Addition of a seazonal component to growth models. - Júnior, Paulo Silveira; Machado, Amauri Almeida (Pesquisa Agropecuaria Brasileira, 2014)
The results of a study of the growth in weight of bovines of the Ibagé race (5/8 Angus - 3/8 Zebu) which adopted the model of Brody for the cubic root of the weight with an additional periodic component lo take into account the seazonal oscillation of the weight are presented. A method to obtain preliminary estimates of the parameters to initiate the iterative process is also presented. The cubic root transformation was used in order to attain homogeneity of variance. Besides homogenizing the variance, this transforrnation facilitated the theoretical treatment of the model